Genotypic tropism testing of proviral DNA to guide maraviroc initiation in aviraemic subjects: 48‐week analysis of results from the PROTEST study. Issue 7 (30th December 2016) - Poveda, E; Hernández‐Quero, J; Pérez‐Elías, MJ; Ribas, MA; Martínez‐Madrid, OJ; Flores, J; Navarro, J; Gutiérrez, F; García‐Deltoro, M; Imaz, A; Ocampo, A; Artero, A; et al.
Abstract : Objectives: Maraviroc (MVC) is a suitable drug for aviraemic subjects on antiretroviral treatment (ART) developing toxicity. Its prescription requires prior tropism testing. It is unknown if proviral DNA genotypic tropism testing is reliable for guiding MVC initiation in aviraemic subjects, so this study was carried out to address this issue. Methods: PROTEST was a phase 4, prospective, single‐arm clinical trial carried out in 24 HIV care centres in Spain. MVC‐naïve HIV‐1‐infected patients with HIV‐1 RNA < 50 copies/mL on stable ART during the previous 6 months who required an ART change because of toxicity and who had R5 HIV, as determined by proviral DNA genotypic tropism testing, initiated MVC with two nucleoside reverse transcriptase inhibitors (NRTIs) and were followed for 48 weeks. Virological failure was defined as two consecutive viral load measurements > 50 copies/mL. Results: Tropism results were available for 141 of 175 (80.6%) subjects screened: 60% had R5 and 85% of these ( n = 74) were finally included in the study. Previous ART included protease inhibitors (PIs) in 62% of subjects, nonnucleoside reverse transcriptase inhibitors (NNRTIs) in 36%, and integrase inhibitors (INIs) in 2%. Main reasons for treatment change were dyslipidaemia (42%), gastrointestinal symptoms (22%) and liver toxicity (15%). MVC was given alongside tenofovir (TDF)/emtricitabine (FTC) (54%) and abacavir (ABC)/lamivudine (3TC) (40%) in most patients. Eighty‐four per cent of patients maintained a viral load < 50 copies/mL to week 48, whereas 16% discontinued treatment: two withdrew informed consent, one had an R5 to X4 shift between screening and baseline, one was lost to follow‐up, one developed an adverse event (rash), two died from non‐study‐related causes, and five developed protocol‐defined virological failure. Conclusions: Initiation of MVC plus two NRTIs in aviraemic subjects based on genotypic tropism testing of proviral HIV‐1 DNA is associated with low rates of virological failure for up to 1 year.